DESIGN AND CONSTRUCTION OF HOUSEHOLD WASTE WATER CLEANER BASED ON ARDUINO - Agung, Ahmad Setyo; Sujono, Sujono (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2021)
ABSTRACT Research program to make household wastewater purifiers using arduino-based control system, This system is from microcontrollers that can work automatically, in the manufacture of systems using filtration materials from cotton, pumice, gravel and sand .after the material has been determined can be started water filtration using turbidity sensors to know the results of water clarity , with the knowledge of this tool can help the community to manage the murky water to be used as clear water in the need of return and can also help the community to get clean water someday in the event of drought, In this program is taught how to make and utilize the latest technology such as household wastewater treatment using electronic devices such as Arduino combined with a turbidity Sensor Keywords: Arduino, Household wastewater purifier, tubidity sensor